EXPERIENCES OF PROVIDERS OF CARE FOR INSTITUTIONALIZED ELDERLY PEOPLE DURING THE COVID-19 PANDEMIC: A QUALITATIVE PERSPECTIVE - Godoy-Pozo, Jéssica; Illesca-Pretty, Mónica; Rosas, Carola; González-Osorio, Luis; Flores, Elizabeth (Cogitare Enfermagem, 2023)
Objective: Uncover the experiences of caregivers of elderly people living in long-term care institutions, during confinement in the context of the Covid-19 pandemic. Method: Qualitative, descriptive research, through an intrinsic case study. Intentional sample by criteria and convenience of six caregivers, Los Ríos Region, Chile; a semi-structured interview was carried out in 2021. Analysis applying the constant comparative method and progressive focusing approach. Validity was ensured by compliance with the criteria of rigor and researcher triangulation. Results: 489 units of meaning gave rise to four thematic groups: Meaning of having lived the experience, facilitating factors, hindering factors and recommendations. Two domains emerged: Contribution of caregivers to strengthening their role during the pandemic and Contribution to strengthening management. Conclusions: it allows recognizing and validating the emotional bond, commitment and vocation of care providers, key aspects to be reinforced through counseling and training to guarantee the quality of care.